Failure Mechanism Analysis of Mechanical Components Under Extreme Conditions (Strojniški vestnik – Journal of Mechanical Engineering, 2024)
This research analyzes failure mechanisms of mechanical components subjected to extreme environmental conditions. Numerical simulation techniques were used to investigate stress concentration, deformation behavior, and damage evolution. The findings provide valuable guidance for improving component safety and durability.
Keywords: Mechanical failure; Extreme conditions; Failure mechanism; Stress analysis; Reliability engineering